Effect of inoculum levels and final pH values on the antioxidant properties of black glutinous rice solution fermented by Lactobacillus bulgaricus - Sripo K. (2017)
© All Rights Reserved. Black glutinous rice is known to have an antioxidant property due to the presence of phenolic compounds and anthocyanin. In this study, the antioxidant properties of black glutinous rice solution fermented by Lactobacillus bulgaricus were determined at different final pH values. Black glutinous rice grain was milled to become powder with the size of less than 595 μm, soaked in distilled water at a ratio of 1:5 for 30 min at room temperature and heated at 95±1°C for 30 min. The heated rice solution that had a pH of 5.90±0.00 was aseptically inoculated with Lb. bulgaricus at a level of 10 4 to 10 7 cfu/ml and incubated at 41±1°C until the pH of the fermented rice solution reached a value of 4.0, 4.5 or 5.0. During the fermentation time, the number of Lb. bulgaricus increased between 1.33 and 4.33 log cfu/ml. Both parameters of lactobacilli inoculation levels and final pH values of the fermented rice solution affected the antioxidant properties of the final rice product. At a final pH of 4.5, the level of anthocyanin improved from 15.43±1.05 to 23.15±0.16 mg/g when the inoculation levels of Lb. bulgaricus increased from 4.0 to 7.0 log cfu/ml. A similar finding was also found for phenolic compounds of the fermented rice solution at a final pH of 4.0. On the other hand, the content of phytic acid decreased from 17.92±2.19 to 5.59±2.69 μg phytic acid equivalents/ml in the fermented rice solution as the inoculation levels of the lactobacilli increased, irrespectively to the final pH value. The highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity was determined in the fermented rice solution added with the lowest inoculation level of Lb. bulgaricus when the final pH values of rice solution were 4.0 and 4.5. A combination of an inoculation level of 7.0 log cfu/ml Lb. bulgaricus and a final pH of 4.5 produced a fermented rice solution with the highest anthocyanin (23.15±0.16 mg/g) and phenolic contents (114.93±1.66 μg gallic acid equivalents/g) and the lowest phytic acid of 5.59±2.69 μg phytic acid equivalents/ml.